Behavioural changes and muscle strength in Rattus norvegicus experimentally infected with Toxocara cati and T. canis. Issue 4 (July 2015) - Santos, S.V.; Moura, J.V.L.; Lescano, S.A.Z.; Castro, J.M.; Ribeiro, M.C.S.A.; Chieffi, P.P.
Abstract Toxocara canis and Toxocara cati are nematode parasites in dogs and cats, respectively, transmitted by ingestion of embryonated eggs, transmammary and transplacental (T. canis) routes and paratenic host predation. Many parasites use mechanisms that change the behaviour of their hosts to ensure continued transmission. Several researchers have demonstrated behavioural changes in mouse models as paratenic hosts for T. canis. However, there have been no studies on behavioural changes in laboratory rats (Rattus norvegicus) experimentally infected with T. cati. This study investigated behavioural changes and muscle strength in male and female rats experimentally infected with T. cati or T. canis in acute and chronic phases of infection. Regardless of sex, rats infected with T. cati showed a greater decrease in muscle strength 42 days post infection compared to rats infected with T. canis. However, behavioural changes were only observed in female rats infected with T. canis.